Best practice: setting up and operating a mid-sized cryo-EM facility - Meng, Xing; Ratnayake, Ishara; Escobar Galvis, Martha L.; Kotecki, Jason; Ramjan, Zack; Zhao, Gongpu (Frontiers in Molecular Biosciences, 2023)
Ever since the resolution revolution in 2013, cryo-electron microscopy (cryo-EM) has become a powerful methodology in structural biology that is especially suited to study the structure of large flexible molecular complexes. Since then, the need of setting up state-of-the-art cryo-EM facilities around the world has increased tremendously. Access to high-end cryo-EM instrumentation is however expensive and requires expertise. The establishment of large cryo-EM centers worldwide, many of which provide academic users free access for both data collection and user training, has been possible with the support of government agencies across the globe. In addition, many universities, and private institutions like the Van Andel Institute (VAI) have made significant investments to establish their own cryo-EM core facilities, ensuring on-site access to their researchers. This paper aims to serve as a blueprint for establishing a new mid-sized cryo-EM facility, as it provides key information based on our experience at VAI and discusses strategies used to optimize routine operation towards high performance and efficiency for single-particle cryo-EM. Information regarding initial planning, selection of equipment as well as the development of IT solutions that were required to improve data collection and analysis are included. In addition, we present an account of the most common issues affecting operation as well as the needs for maintenance over a six-year period, which can help interested parties to estimate the long-term costs of running this type of facility. Lastly, a brief discussion on the pros and cons of establishing the facility is also included.